Role of EtMIC4 EGF-like in regulating the apoptosis of Eimeria tenella host cells via the EGFR pathway - Xue-song Zhang; Yong-juan Zhao; Yu Zhang; Tong Xu; Kai-ling Cui; Bu-ting Duan; Xiao-ling Lv; Li Zhang; Zhi-yong Xu; Rui Bai; Ming-xue Zheng (Poultry Science, 2022)
This study aimed to explore the role and key point of EtMIC4 EGF-like recombinant protein in regulating the apoptosis of Eimeria tenella host cells via the epidermal growth factor receptor (EGFR) pathway. The cells were treated with EtMIC4 EGF-like protein, EGFR-specific siRNA, or both. Infection and apoptosis rates as well as dynamic changes in the key genes and proteins of the EGFR signaling pathway in the host cells were determined. Results showed that the E. tenella and EtMIC4 EGF-like group had the highest infection rate (P < 0.01). In cells treated with EtMIC4 EGF-like for 4 to 24 h, the apoptosis rate was significantly decreased (P < 0.01) and the relative mRNA expression and protein phosphorylation levels of EGFR, protein kinase B (AKT), and extracellular regulated protein kinases (ERK) were significantly increased (P < 0.01). In E. tenella sporozoites infected for 4 to 96 h, the rate of host cell apoptosis induced by E. tenella infection was significantly (P < 0.01) reduced by EtMIC4 EGF-like. The relative mRNA expression and protein phosphorylation levels of EGFR, AKT, and ERK in the host cells of E. tenella + EtMIC4 EGF-like group were significantly increased (P < 0.01). These results indicated that E. tenella could activate the EGFR pathway through EtMIC4 EGF-like and regulate the expression of key genes in the AKT and ERK signaling pathways, thereby inhibiting cell apoptosis.